Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

A+b = 76

a-b = 38

by adding the two equations,

2a = 76+38 = 114

⇒a = 114/2 =

a+b = 76

⇒57 + b = 76

⇒ b = 76 - 57 =

a-b = 38

by adding the two equations,

2a = 76+38 = 114

⇒a = 114/2 =

**57**a+b = 76

⇒57 + b = 76

⇒ b = 76 - 57 =

**19**a - b = 38 consider this as equation (2)

let equation (1 ) & (2 ) we get,

a + b = 76

a - b = 38 (+ )

.................

2a = 114

a = 114/ 2

a = 57,

apply the value of a in any of those two equations to get the b value,

let i take the equation (1 )

substitute a value in equation 1 we get,

57 + b = 76

b = 76 - 57

b = 19

therefore a = 57 , b = 19,

if u want to check whether the answers correct apply these two values in any of those equations

let i take equation 2

a - b = 38

57 - 19 = 38

38 = 38,

so the values are correct